ACM's Annual Report. - Chesnais, Alain (Communications of the ACM, 2012)
The article offers an annual report for the Association for Computing Machinery (ACM) society for the year 2011. Topics discussed include improvements to ACM's digital libraries, the establishment of the Computing in the Core coalition to encourage computer science education at the elementary through secondary levels, and the launch of an ACM branch in China. Also considered is ACM's work to shape public policy and legislation, awards given to computer science college students at the 35th Annual ACM International Collegiate Programming Contest (ICPC), and the Grace Hopper Celebration meeting for women in computer science.